PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PADA CV. PLAZA MEUBEL MASRUM PEKANBARU - kurniawan, teuku reza (Eko dan Bisnis: Riau Economic and Business Review, 2020)
Abstract : This research was conducted at CV. Plaza Meubel Masrum Pekanbaru, which is engaged in selling teak, which is located at Jalan HR.Soebrantas KM 9 No 175 Panam Pekanbaru. The purpose of this study was to determine the influence of leadership on Employee Motivation at CV. Plaza Meubel Masrum Pekanbaru. The population in this study were 30 employees. In this study, sampling using the Census Sampling technique, amounting to 30 employees. The data used are primary and secondary data with analysis using simple linear regression. The results showed Y = 7,015 + 1,039X and the t test showed that t count> t table (10,178> 2,04841) this means that leadership has a significant effect on employee motivation at CV. Plaza Meubel Masrum Pekanbaru. The level of influence of leadership on motivation is 78.7% while the remaining 21.3% is influenced by other variables.Â Â